Between Brazilian Arbitration and European Arbitration: A study about the National Telecommunications Agency (ANATEL) and the Office of Communications (OFCOM) - Kelvin Lashon (International Journal of Science and Society, 2022)
The search for arbitration as a means of resolving disputes is important due to the large volume of cases submitted to the judgment of the State - judge, in a number inversely proportional to the technical preparation of those who are invested in the jurisdictional function by state act. Currently, talking about extrajudicial settlement of conflicts in the field of regulation means entering a scenario of great discussions and debates. In this way, the text seeks to build reasons for the resolution of disputes in the field of telecommunications through arbitration, including, in view of the European experience, such as OFCOM. One of the duties of the regulatory agencies is precisely the solution of conflicts between players in the sector at the administrative level. When analyzing the forms of dispute resolution in the European Union, a peculiar behavior can be highlighted. In major disputes that occur on the continent, it is more common to use arbitration than the judiciary. In fact, arbitration can be used by ANATEL as an important tool to ensure a broad, free and fair competition between providers of telecommunications services, as it dodges the slowness of the judiciary and the possibility of sham litigations, enabling the rapid adoption of a decision that often affects the rights of a large number of users of telecommunications services. The high prestige enjoyed by these methods of dispute resolution pays homage to their characteristic of being a neutral forum positioned far from a regulatory agency of a specific country and close to referees chosen by common agreement, or even connected to international institutions that provide the arbitration services in commercial disputes.